Dynamics of Th17 cells and their role in Schistosoma japonicum infection in C57BL/6 mice. - Xiaoyun Wen; Lei He; Ying Chi; Sha Zhou; Jason Hoellwarth; Cui Zhang; Jifeng Zhu; Calvin Wu; Shawn Dhesi; Xuefeng Wang; Feng Liu; Chuan Su (Public Library of Science (PLoS), 2011)
BACKGROUND: The current knowledge of immunological responses to schistosomiasis, a major tropical helminthic disease, is insufficient, and a better understanding of these responses would support vaccine development or therapies to control granuloma-associated immunopathology. CD4(+) T cells play critical roles in both host immune responses against parasitic infection and immunopathology in schistosomiasis. The induction of T helper (Th)1, Th2 and T regulatory (Treg) cells and their roles in schistosome infections are well-illustrated. However, little in vivo data are available on the dynamics of Th17 cells, another important CD4(+) T cell subset, after Schistosoma japonicum infection or whether these cells and their defining IL-17 cytokine mediate host protective responses early in infection. METHODOLOGY: Levels of Th17 and the other three CD4(+) T cell subpopulations and the cytokines related to induction or repression of Th17 cell generation in different stages of S. japonicum infection were observed. Contrary to reported in vitro studies, our results showed that the Th17 cells were induced along with the Th1, Th2, Treg cells and the IFN-γ and IL-4 cytokines in S. japonicum infected mice. The results also suggested that S. japonicum egg antigens but not adult worm antigens preferentially induced Th17 cell generation. Furthermore, decreasing IL-17 with a neutralizing anti-IL-17 monoclonal antibody (mAb) increased schistosome-specific antibody levels and partial protection against S. japonicum infection in mice. CONCLUSIONS: Our study is the first to report the dynamics of Th17 cells during S. japonicum infection and indicate that Th17 cell differentiation results from the integrated impact of inducing and suppressive factors promoted by the parasite. Importantly, our findings suggest that lower IL-17 levels may result in favorable host protective responses. This study significantly contributes to the understanding of immunity to schistosomiasis and may aid in developing interventions to protect hosts from infection or restrain immunopathology.